Application of Acupoint Catgut Embedding Therapy Combined with Liuzijue Breathing Exercise in the Treatment of Patients with Stable Chronic Obstructive Pulmonary Disease. (6th October 2022) - Zheng, Yun; Xia, Jing; Zheng, Jisheng
Abstract : Objective . To evaluate the application value of acupoint catgut embedding therapy combined with Liuzijue breathing exercise in the treatment of patients with stable chronic obstructive pulmonary disease (COPD) and its impact on immune function and quality of life. Methods . A total of 100 patients with stable COPD admitted to our hospital from February 2020 to February 2021 were included and assigned to the experimental group ( n = 50) and the control group ( n = 50) according to the order of admission. Both groups of patients received conventional treatment. The control group was given daily inhalation of budesonide and formoterol fumarate powder for inhalation (320 ug/bottle), and the experimental group received additional acupoint catgut embedding therapy combined with Liuzijue breathing exercise. The clinical efficacy, pulmonary function indexes, activities of daily living (ADL) scores, quality of life (QOL) scores, traditional Chinese medicine (TCM) syndrome scores, the number of acute exacerbations, medical expenses, the incidence of adverse reactions, and immune indicators were compared between the two groups of patients. Results . The experimental group yielded a significantly higher effective rate of treatment than the control group (P < 0.05 ). After the treatment, the experimental group obtained a superior outcome in terms of lung function indexes, immune function indexes, ADL and QOL scores, and the TCM syndrome scores when compared with the control group (P < 0.05 ). The number of acute exacerbations in the experimental group was remarkably lower than that in the control group (P < 0.05 ). No serious adverse reactions were observed in the two groups of patients, and no significant difference in the incidence of adverse reactions was found (P > 0.05 ). Conclusion . Acupoint catgut embedding therapy combined with Liuzijue breathing exercise, with high safety, can improve the treatment effect and the quality of life of patients with stable COPD, which merits clinical promotion.